Drug development and bioanalytical method validation for a novel anticancer molecule, 4‐(dimethylamino)‐2‐(p‐tolylamino) thiazole‐5‐carbonitrile. Issue 8 (17th October 2018) - Biswas, Nripendra Madhab; Shard, Amit; Patel, Sagarkumar; Sengupta, Pinaki
Abstract : Hit, Lead & Candidate Discovery The thiazole ring system represents a significant building block that exists in many biologically active natural products and clinically successful anticancer drugs. Modifications of the thiazole core have been a proven and highly effective method in improving anticancer potency. We designed a novel thiazole‐based molecule, 4‐(dimethylamino)‐2‐(p‐tolylamino) thiazole‐5‐carbonitrile, which showed potent in vitro anticancer effect against targeted Bcl‐2 Jurkat cell‐line quantified using 3‐(4, 5‐dimethythiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide (MTT) assay. Physicochemical parameters (pKa, LogP, LogD) of the molecule have also been evaluated as a part of the drug development process. Moreover, a rapid Reverse phase‐high performance liquid chromatography (RP‐HPLC) bioanalytical method has been developed to quantitate the molecule in human plasma. The method has been validated following the United States Food and Drug Administration bioanalytical method validation guideline. The stability studies showed no significant instability of the analyte in respective stability conditions (6 hr autosampler, 8 hr bench top, 30 days long‐term, and 3 freeze–thaw cycles). The molecule was found to be stable for 3 hr in human plasma. The molecule was shown to have high plasma protein binding affinity. It showed favorable pKa (11), Log P (3.01), Log D (2.96), and plasma protein binding (90%) values toward its further exploitation as a lead anticancer candidate molecule. The developed bioanalytical method can be used for quantifying the molecule in different pharmacokinetic, toxicokinetic, or other clinical trial samples involving human plasma during development process or in routine bioavailability and bioequivalence study after its regulatory approval.